Priorities and actions for Latin American integration: an approximation - González Izquierdo, Jorge (Universidad del Pacífico, 1993)
​This essay analyzes the economic integration process among Latin American countries. These countries followed a model of import-substitution industrialization (ISI). This kind of policies did not permit sustained growth, but they can be promoted by economic and commercial integration of the region. This integration must be part of the new trends of world development based on the economic globalization. Furthermore, it should be oriented toward coordination of macroeconomic policies among participants